Environmental Education in Indonesia Creating Responsible Citizens in the Global South? - Parker, Lyn (Routledge Explorations in Environmental Studies, 2020)
Indonesia's wealth of natural resources is being exploited at breakneck speed, and environmental awareness and knowledge among the populace is limited. This book examines how young people learn about the environment to see how education can help to develop environmental awareness and avert vast environmental destruction, not only in Indonesia, but also in the Global South more generally. Based on in-depth studies conducted in the cities of Yogyakarta and Surabaya, complemented with surveys of students in secondary schools, Environmental Education in Indonesia examines educational curricula, pedagogy and "green" activities to reveal what is currently being done in schools to educate children about the environment. The book investigates the shortcomings in environment education, including underqualified teachers, the civil service mentality, the still-pervasive chalk-and-talk pedagogy and the effect of the examination system. It also analyses the role of local government in supporting (or not) environmental education, and the contribution of environmental NGOs. The book establishes that young people are not currently being exposed to effective environmental education, and the authors propose that the best and most culturally appropriate way forward in Indonesia is to frame pro-environment behaviour and responsibility as a form of citizenship, and specifically that environmental education should be taught as a separate subject. This book will be of great interest to students and scholars of contemporary Indonesia and Southeast Asia, education for sustainability and environmental education, as well as sustainability and sustainable development more generally. The Open Access version of this book, available at http://www.tandfebooks.com/doi/view/10.4324/9780429397981, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.